ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENERIMAAN PAJAK BUMI DAN BANGUNAN (STUDI KASUS PADA SEMARANG TENGAH) (Students' Journal of Accounting and Banking, 2014)
The purpose of this research is to analyze about the awareness of paying taxes, understanding of the taxpayer, the taxpayer's attitude, on the priorities development of the Government, the ability of taxpayers to the tax collection system, the success of the tax revenue. This research was carried out at the Tax Services Office in Semarang.The population in this study is mandatory taxes earth building in Semarang Regional Tax Office amid taxpayer numbering 6,890, while the sample in the study is the taxpayer who pays taxes earth building, the sampling method used is random sampling and obtaining samples of 100 samples are required tax, then tested with multiple regression.The results obtained in this research is in the consciousness of the taxpayer, the taxpayer's understanding, the attitude of the taxpayer on priorities construction of the Government, the ability of the taxpayer, the tax collection system is very positive effect on the success of the tax revenue.Keywords: awareness of the taxpayer, the taxpayer's understanding, the attitude of the taxpayer against the Government's development priorities, the ability of the taxpayer, voting systems, and the success of Earth and building tax receipt